2018
DOI: 10.1016/j.psychres.2018.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment and impulsivity as predictors of interpersonal violence, self-injury and suicide attempts: A national study

Abstract: Prior research indicates that childhood maltreatment and impulsivity increase the risk for different types of violence, including violent behaviors directed toward the self and others. However, it is not known whether childhood maltreatment and impulsivity have independent effects on different violent behaviors. Therefore, this study examined the differential effects of childhood maltreatment and impulsivity on interpersonal violence, suicide attempts, and self-injury. Data were drawn from a nationally represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 81 publications
3
48
0
2
Order By: Relevance
“…The severity of impulsiveness, however, played a more important role in self-injury than interpersonal violence or suicide attempts. Their study thus concluded that the childhood maltreatment experience and impulsivity were probably involved in different types of harmful and aggressive behaviors towards oneself and others (41). In the present study, females impulsivity score was higher than males, suggesting that impulsivity was higher in males than females.…”
Section: Discussionsupporting
confidence: 44%
“…The severity of impulsiveness, however, played a more important role in self-injury than interpersonal violence or suicide attempts. Their study thus concluded that the childhood maltreatment experience and impulsivity were probably involved in different types of harmful and aggressive behaviors towards oneself and others (41). In the present study, females impulsivity score was higher than males, suggesting that impulsivity was higher in males than females.…”
Section: Discussionsupporting
confidence: 44%
“…To the extent that this was the case, prevalence rates are likely to be lower bound estimates. Third, a single-item assessment for both suicidal ideation and attempt was adopted, which may bias results towards an inflation of prevalence estimates due to misclassification (Millner, Lee, & Nock, 2015). In doing so, we were unable to capture the frequency or severity of suicidal outcomes -both the attempt and ideation groups therefore reflect a heterogeneous 984 FROM IDEATION TO ACTION composition of suicidal individuals.…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…We also found that aggression was significantly associated with attempted suicide in women. This factor could have an overlap with suicidal behavior, interpersonal aggression, and self-harm as a spectral event, in which some subjects may engage in one of these different types of violent behavior [84,85]. Interestingly, it is suggested that aggression and impulsivity are diathesis factors in suicidal behavior [86,87].…”
Section: Plos Onementioning
confidence: 99%